2015
DOI: 10.1016/j.joca.2015.02.986
|View full text |Cite
|
Sign up to set email alerts
|

Developmental switch in SOX9 expression in articular cartilage is regulated by epigenetic histone methylation

Abstract: intermediate (inner lateral tibial plateaus, iLT) and late stage (inner medial plateaus, iMT) of OA in Japanese. Methods: Genome-wide DNA methylation analysis was performed using Illumina Infinium HumanMethylation450 BeadChip array on DNA extracted from the cartilage of oLT, iLT and iMT region of 8 patients. Raw IDAT files were analyzed using package "minfi" in R. Data was normalized through SWAN (subquantile normalization) method. Multidimensional scaling (MDS) was used to identify the outliers. Probes that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…No histopathological features of osteoarthritis were observed in examined joints by 18 months. Epigenetic study revealed that the reduction of SOX9 expression in ACs of adult mice is primarily regulated by H3K4me2 (a histone modification for transcriptional activation) (Zhang et al, 2015a). miRNA-145 has been identified as an inhibitor of SOX9 expression in human cartilage and chondrosarcoma (Mak et al, 2015); increased miRNA-145 directly represses SOX9 expression, causing reduced expression of COL2A1 and aggrecan with an increased level of MMP13 (Martinez-Sanchez et al, 2012).…”
Section: Epigenetic Mechanisms Underlying the Aberrant Metabolic Amentioning
confidence: 99%
“…No histopathological features of osteoarthritis were observed in examined joints by 18 months. Epigenetic study revealed that the reduction of SOX9 expression in ACs of adult mice is primarily regulated by H3K4me2 (a histone modification for transcriptional activation) (Zhang et al, 2015a). miRNA-145 has been identified as an inhibitor of SOX9 expression in human cartilage and chondrosarcoma (Mak et al, 2015); increased miRNA-145 directly represses SOX9 expression, causing reduced expression of COL2A1 and aggrecan with an increased level of MMP13 (Martinez-Sanchez et al, 2012).…”
Section: Epigenetic Mechanisms Underlying the Aberrant Metabolic Amentioning
confidence: 99%